2007
DOI: 10.1002/pssa.200622155
|View full text |Cite
|
Sign up to set email alerts
|

Determination of atom displacement distribution in YBCO superconductors induced by gamma radiation

Abstract: The calculation results of the atom displacement distribution induced by gamma radiation in the superconducting material YBa2Cu3O7–x are presented. Firstly, a direct calculation procedure for the atom displacement distribution inside a given material is introduced, starting from the application of the energy flux distribution values of secondary electrons, formerly calculated using the Monte Carlo method based code system MCNP‐4C. Finally, calculation results of the atom displacement distribution, regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…However, Piñera et al had shown by means of Monte Carlo Methods assisted gamma quanta transport calculations in YBCO matrix, that Φ(E i , z) does not follow such a "model" dependence on regard of both, E i and z as it is shown in Fig. 2 (Piñera et al, 2007a). …”
Section: Averaging Methods Following Oen -Holmes -Cahn Algorithmmentioning
confidence: 96%
See 4 more Smart Citations
“…However, Piñera et al had shown by means of Monte Carlo Methods assisted gamma quanta transport calculations in YBCO matrix, that Φ(E i , z) does not follow such a "model" dependence on regard of both, E i and z as it is shown in Fig. 2 (Piñera et al, 2007a). …”
Section: Averaging Methods Following Oen -Holmes -Cahn Algorithmmentioning
confidence: 96%
“…4 shows that each atomic specie contributes to atom displacement processes only over a given critical electron kinetic energy E c . A critical evaluation among MCSAD predictions with those previously obtained by Piñera et al and Fukuya-Kimura is in course (Piñera et al, 2007a(Piñera et al, , 2007b(Piñera et al, , 2008a(Piñera et al, , 2008bFukuya & Kimura, 2003). …”
Section: Fig 3 (A) Fukuya's Treatment Of Atom Displacements Processmentioning
confidence: 93%
See 3 more Smart Citations